Can blood glucose levels predict biochemical and hematological abnormalities in Covid -19 patients - Experience from a tertiary care hospital in Balochistan - Bashir, Saima; Azeema Ahmad; Hamid Iqbal; Shafia Nasir; Khurram Haq Nawaz; Zeeshan Ayub (Journal of the Pakistan Medical Association, 2022)
Objective: To find out the association between poor glycaemic levels and biochemical and haematological abnormalities in patients of coronovairus disease-2019. Methods: The prospective, observational, cohort study was conducted at the Combined Military Hospital, Quetta, Pakistan, from September 2020 to February 2021, and comprised all patients who tested positive for coronavirus disease-2019 on polymerase chain reaction test and were subsequently admitted. The patients were divided into two groups on the basis of random blood glucose level at the time of admission; 11.1mmol/l (206mg/dl) in group A, and 4-11.1mmol (74-206mg/dl) in group B. Association between categorical variables was evaluated and hazard ratio was measured. Data was analysed using SPSS 21. Results: Of the 349 patients, there were 56(16%) in group A; 40(71.4%) males and 16(28.6%) females with age range 39-61 years. There were 293(84%) subjects in group B; 239(81.5%) males and 54(18.5%) females with age range 27-53 years. Overall, 75(21.4%) patients were known type 2 diabetics. A significant association was found between poor glycaemic control and raised levels of C-reactive protein, lactate dehydrogenase, ferritin, erythrocyte sedimentation rate, troponin, creatine kinase, reatine kinase-MB, alanine aminotransferase, creatinine and D-dimers (p<0.05). Inter-group differences were significant for acute kidney injury, acute liver injury, Intensive care unit admission for coagulation abnormalities and for overall mortality (p<0.05). Conclusion: Poor glycaemic control was found to be a risk factor for developing multisystem complications in patients of coronavirus disease-2019. Key Words: Biochemical, Covid-19, Hyperglycaemia.